School Based Management System At Utama Widya Pasraman Astika Dharma Karangasem : School Based Management System At Utama Widya Pasraman Astika Dharma Karangasem - I Wayan Sudiarta; I Wayan Winaja; Ni Made Indiani (Universitas Ahmad Dahlan, 2023)
Utama Widya Pasraman Astika Dharma Karangasem is a Hindu religious education unit for high school education, according to Minister of Religion Regulation Number 10 of 2020 concerning Hindu Religious Education. The problems faced are not having their dapodik (primary educational data) house, still joining dapodik from the Ministry of Education and Culture, government assistance is not maximized, the community still considering formal pasraman as nonformal institutions such as weekly pasraman, some people thinking pasraman graduates cannot continue their studies at public tertiary institutions. This study aims to explore and analyze the School-Based Management System at Utama Widya Pasraman Astika Dharma Karangasem, so that later it can contribute to efforts to manage Pasraman. The method used is qualitative, with data analysis consisting of domain analysis, taxonomy, componential, and cultural themes. The study results show that the School Based Management System is applied according to input, process, and output characteristics. In full management implementation, community leaders are involved in improving the quality of education at Utama Widya Pasraman Astika Dharma Karangasem.